2006
DOI: 10.1002/jmv.20594
|View full text |Cite
|
Sign up to set email alerts
|

Vesivirus viremia and seroprevalence in humans

Abstract: Pathogenic caliciviruses of the genus Vesivirus circulate in oceanic ecosystems and spread to and among terrestrial mammals. Isolation of Vesivirus from natural and laboratory infections in humans led to this investigation of Vesivirus seroprevalence and viremia. Sera from four groups were tested for antibodies to Vesivirus as follows: blood donors whose units were cleared for donation, blood donors whose units were not accepted for donation solely because of elevated blood liver alanine aminotransferase (ALT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…It was recently shown that in some cases there was no sharp demarcation of the host species for some calicivirus infections; some caliciviruses may have zoonotic potential, and animals such as domestic pigs may act as a reservoir for noroviruses or vesiviruses (2,22,24). By phylogenetic analysis, a higher degree of genetic diversity was seen among porcine sapoviruses than among the known human sapoviruses, indicating that the coevolution of sapoviruses in swine was longer.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that in some cases there was no sharp demarcation of the host species for some calicivirus infections; some caliciviruses may have zoonotic potential, and animals such as domestic pigs may act as a reservoir for noroviruses or vesiviruses (2,22,24). By phylogenetic analysis, a higher degree of genetic diversity was seen among porcine sapoviruses than among the known human sapoviruses, indicating that the coevolution of sapoviruses in swine was longer.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemics of VESV in North America from the 1930s to 1950s were shown by classical virological investigations to be serotypes of marine origin (56,57,65). SMSV was also found in vesicular lesions in humans, and antibodies were detected in blood donors (54,55).…”
mentioning
confidence: 97%
“…One of the serotypes of San Miguel sea lion virus (SMSV), belonging to the Vesivirus genus, has a list of several natural hosts, including five genera of seals, cattle, three genera of whales, donkeys, foxes, and humans (10,11). A zoonotic potential of SMSV and feline calicivirus (FCV), a member of the Vesivirus genus and a major causative agent of upper respiratory and hemorrhagic diseases in cats (12), is suggested by reports of human antibody against these viruses (10,11,13). Our aim in this study was to provide a structural characterization of a prototype vesivirus and examine the extent of structural complementarity between animal and human caliciviruses.…”
mentioning
confidence: 99%